Bilingualism as a Linguistic Phenomenon and Features of its Functioning - Sabira, Joldasbaeva (European Journal of Life Safety and Stability (2660-9630), 2023)
This article gives more information about Bilingualism and the coexistence of two languages in a person or in the whole people, usually the first - native, and the second - acquired. If knowledge of two languages is characteristic of individual members of society, then this is individual bilingualism, if for large contingents of speakers, then this is mass bilingualism.